Nanocomposite ZnO/g-C3N4 for Improved Degradation of Dyes under Visible Light: Facile Preparation, Characterization, and Performance Investigations - Tu Anh Nguyen Thi; Anh- Tuan Vu (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
In this study, ZnO/g-C3N4 nanocomposites were prepared via a physical mixing-calcination process for improved degradation of dyes under visible light irradiation. The BET surface area, pore volume, crystal size, and pHpzc of the ZnO/g-C3N4 composite were 3.9 m2/g, 0.034 cm3/g, 18.1 nm, and 7.7, respectively. Although the morphology of the ZnO/g-C3N4 composite was very different from that of pure g-C3N4, their average pore sizes were similar. The Eg of the ZnO/g-C3N4 composite (3.195 eV) was slightly lower than that of ZnO (3.195) but much higher than that of g-C3N4 (2.875). The interface interaction of ZnO and g-C3N4, which was revealed by oscillations of Zn-C, benefited the transport of photoinduced charge carriers and reduced the recombination of electron-hole. As the result, the ZnO/g-C3N4 composite had higher photocatalytic activity than ZnO and g-C3N4. Its degradation efficiency (DE) value for methylene blue (MB) in 90 min and rate constant were 93.2 % and 0.025 min‑1, respectively. In addition, the effects of ZnO/urea molar ratio, catalyst dosage, solution pH, and concentration of dye on photocatalytic degradation of MB were completely investigated. The photocatalytic performance of the ZnO/g-C3N4 composite was evaluated by the degradation of other persistent organic compounds, also compared to other catalysts in the literatures. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).